Mulheres denunciam corrupção nas maternidades de Nampula - Voa Português (Voa Português, 2015)
Parteiras exigem entre 500 e 2.000 meticais para realizar partos. Cobranças ilícitas nas maternidades das unidades sanitárias em Nampula, Moçambique, estão a comprometer a qualidade do atendimento materno-infantil e a “forçar” as grávidas a optarem por ter filhos na comunidade. Algumas mulheres ouvidas pela VOA no Hospital Central de Nampula denunciaram o mau atendimento nas unidades sanitárias. Acusam ainda profissionais de cobrarem entre 500 e 2.000 meticais para realizar um parto.
Keywords: G - Mozambique / Moçambique; GP - Nampula; L - portuguese / português; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude